Ownership transformation of spa resorts in the Republic of Serbia (the model of the privatization of Gornja Trep?a Ltd., Gornja Trep?a) - Ljubisavljević, Tijana; Radosavljević, Zoran (Hotel and Tourism Management, 2018)
The subject of this paper is an explanation of the concepts of ownership, ownership transformation and detailed analysis of the key elements in the business operations of Gornja Trep?a Spa Ltd., Gornja Trep?a, before and after privatization. The aim of this paper is to present a good example of a privatization through the analysis of the key elements that are responsible for successful spa business. The importance of this work is in its very goal, which is to draw attention to the significance of spa resorts and ownership transformation that is still in progress in the Republic of Serbia. An example of successfully implemented privatization can serve as a model for all remaining unresolved problems in the field of transformation of the properties of spa resorts.